Experience and Expectation of Socialism: Principle versus Practice in Nepal - Paudel, Rudra Prasad (Molung Educational Frontier, 2023)
This article discusses Nepali people’s experience with socialism and their expectations by addressing these questions: What is socialism? Which socialism do Nepali people expect? Why do they expect socialism? How does the principle go against the practice in the context of Nepal? Qualitative secondary sources are critically analyzed as methodological tools to reveal the present experience and expectations of Nepali people. It presents the disparity between principle and practice demonstrated by the Nepali political parties. The Constitution of Nepal2015 has formally promised that the guiding political-economic principle of this state is socialism-oriented. However, the sayings and doings of major political parties in Nepal have a big gap. In their doings, they are highly influenced by liberal capitalist principles, and they continue implementing neo-liberal policies. They put forward liberal bourgeois policies and programs that suited the interest of the comprador bourgeoisie. Thus, we have seen a contradiction in their implementation of the socialist principle, which goes against the expectation of the Nepali people. By pointing out this gap, this article highlights the need for serious discussions on achieving socialism as stated in Nepal’s constitution and expected by the people while also drawing the attention of the political actors to take immediate and radical actions to correct their behaviors in time in order to achieve the goal of a Socialism Nepal.